2020
DOI: 10.1002/ange.202012164
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Markovnikov‐Type Selective Hydroboration of Terminal Alkynes

Abstract: A cobalt-catalyzed Markovnikov-type hydroboration of terminal alkynes with HBpin to access a-alkenyl boronates with good regioselectivity and atom economy is reported. A new ligand has been developed for the cobalt hydride catalyst that has been used for a unique Markovnikov selective insertion of terminal alkynes into metal hydride bond. This operationally simple protocol exhibits excellent functional group tolerance to deliver valuable alkene derivatives. Scheme 1. Metal-catalyzed selective hydroboration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Moreover, complex 3 with two UhCo triple bonds displays excellent catalytic activity and selectivity in the formation of a-vinylboronate 7a at RT and with a 2.5 mol% catalyst load (entry 8), which is comparable with the best result reported previously. 51 No hydroboration activity was observed when either complex 4 or 5 was used at RT in this model reaction, and only poor yields and selectivity were observed at 75 C (entries 9 and 10), which is consistent with the less successful iron-catalyzed hydroboration of alkynes. 52 These experiments show that the cooperativity between uranium and cobalt is important for the selective formation of the Markovnikov-type hydroboration product 7a by the reaction of phenylacetylene with HBpin.…”
Section: Catalytic Activitysupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, complex 3 with two UhCo triple bonds displays excellent catalytic activity and selectivity in the formation of a-vinylboronate 7a at RT and with a 2.5 mol% catalyst load (entry 8), which is comparable with the best result reported previously. 51 No hydroboration activity was observed when either complex 4 or 5 was used at RT in this model reaction, and only poor yields and selectivity were observed at 75 C (entries 9 and 10), which is consistent with the less successful iron-catalyzed hydroboration of alkynes. 52 These experiments show that the cooperativity between uranium and cobalt is important for the selective formation of the Markovnikov-type hydroboration product 7a by the reaction of phenylacetylene with HBpin.…”
Section: Catalytic Activitysupporting
confidence: 69%
“…42 Although b-vinylboronates have been synthesized by the hydroboration of terminal alkynes, a reaction catalyzed by various transition metal catalysts, [43][44][45][46][47] the selective synthesis of a-vinylboronates via hydroboration of terminal alkynes has been less explored. [48][49][50][51][52] Therefore, the development of a new catalytic system for the direct one-step hydroboration of alkynes to a-vinylboronates is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In the past decades, metal-catalyzed hydroboration has been extensively investigated. [19][20][21][22][23][24][25][26][27][28][29][30] Nevertheless, the electrochemically catalyzed hydroboration has been rarely reported to form the corresponding boronates. 31,32 Quite recently, Qing et al reported the electrocatalytic hydroboration of aryl alkenes with HBpin; however, an additional 0.8 equivalents of N,N-diisopropylethylamine as an additive was required to promote the formation of products.…”
Section: Introductionmentioning
confidence: 99%